Педагогічні умови формування мотивації навчання дітей з особливими освітніми потребами - Зима-Клекоць, Дмитро Анатолійович (Луцьк : ЛНТУ, 2025)
У роботі досліджено: у першому розділі розкриті теоретичні засади формування мотивації навчання дітей з особливими освітніми потребами: визначено зміст поняття мотивації навчання та її значення в педагогічному процесі; охарактеризовані особливості навчальної мотивації дітей з ООП; виділені психолого-педагогічні підходи до формування мотивації навчання в інклюзивному освітньому середовищі. У другому розділі визначені педагогічні умови та технологія формування мотивації навчання дітей з ООП: досліджені педагогічні умови формування мотивації навчання дітей з особливими освітніми потребами; розроблені методичні рекомендації щодо впровадження педагогічних умов в освітнє інклюзивне середовище.

The work explores: in the first section, the theoretical principles of the formation of learning motivation in children with special educational needs are revealed: the content of the concept of learning motivation and its significance in the pedagogical process are defined; the features of the learning motivation of children with special educational needs are characterized; psychological and pedagogical approaches to the formation of learning motivation in an inclusive educational environment are highlighted. In the second section, the pedagogical conditions and technology for the formation of learning motivation in children with special educational needs are defined: the pedagogical conditions for the formation of learning motivation in children with special educational needs are investigated; methodological recommendations for the implementation of pedagogical conditions in an inclusive educational environment are developed.
Pedagogical Conditions for the Formation of Learning Motivation of Children with Cpecial Educational Needs.
Keywords: мотивація навчання; педагогічні умови; дітей з особливими освітніми потребами; технологія